Spontaneous adverse drug reaction reporting by community pharmacists: preparedness and barriers - Mohamed Bahlol; Mary Bushell; Hani M.J. Khojah; Rebecca Susan Dewey (Elsevier, 2022)
Background: Adverse drug reactions (ADRs) are undesired, unintended responses to drugs, and are significantly underreported. Pharmacists are drug experts recognized as custodians of drug safety, who are expected to be prepared for and knowledgeable about ADR reporting. Objectives: To identify Egyptian community pharmacists' preparedness for and perceived barriers to spontaneous ADR reporting. Methods: This cross-sectional study recruited a sample of community pharmacists across Egypt, who were invited to complete a self-administrated questionnaire during April 2020. Results: A total of 923 pharmacists across Egypt responded to the questionnaire. Most pharmacists were knowledgeable about the definition of ADRs (93.9 %) and indicated they felt reporting ADRs benefits the patients (82.2%). Despite recognizing their public health value, only a small percentage of participants conveyed familiarity with the reporting process for both paper (19.2%) and electronic (30.4%) forms, indeed 56.6% of participants did not remember what the ADR report form looked like. Moreover, 75.4% of respondents said they felt that community pharmacies are not the right place for reporting, with 49% suggesting that reporting was the responsibility of physicians. However, only 32.1% reported having insufficient time being a barrier to ADR reporting. Conclusions: Community pharmacists in Egypt are not well prepared for spontaneous ADR reporting due to a lack of knowledge about the formal process and not acknowledging their responsibility, although time was not a major barrier. Therefore, this highlights a clear opportunity for improvement likely involving targeted education.